TINJAUAN DESAIN TRACER BERKAS REKAM MEDIS DALAM MENCEGAH KEJADIAN MISSFILE GUNA MENUNJANG KELANCARAN PELAYANAN DI RSAU LANUD SULAIMAN BANDUNG - Monica, Rizqy Dimas; Rahmatika, Shabila Rizky; Pujilestari, Intan; Trianto, Wowo; Nulhakim, Luqman (Jurnal TEDC, 2024)
The results of the Preliminary Study when searching for medical record documents there were missfile incidents of 10 medical record documents, with 4 medical record files in March, 3 medical record files in April, and 3 medical record files in May. This is because the storage room at Sulaiman Air Force Air Force Base is still a mess The research method used is descriptive method with a qualitative approach. The subjects in this study were medical record officers, the object of this study was the procedure for using medical record file tracers. Data collection techniques used are observation, interviews, and documentation. The results of the research conducted by the author, show that the data for taking medical record files in March were 150 medical record files, the occurrence of missfiles was 4 medical record files due to an error in the sequence of numbers and file storage errors, in April there were 120 medical record files, 3 medical record files due to errors in the order of numbers, reading errors, and mistaking numbers, while in May there were 100 medical record files with missifles as many as 3 medical record files due to sequence errors and file storage errors. The tracer used is 10.5 x 32 cm in size, yellow and orange. The constraints on using a tracer to prevent missfile incidents are the time factor, the accuracy factor, the expedition book and the storage rack. Efforts were made to overcome the problem of using a tracer in preventing missfile incidents, namely if the medical record file is not found, the storage officer will create a medical record file to replace the missing medical record file.